A Study on the Security Algorithm for Contexts in Smart Cities - Hoon Ko; Kitae Bae; Sang Heon Kim; Kyung Jin An (International Journal of Distributed Sensor Networks)
Recently, a great number of smart devices associated with their users exist within Smart City. Users are constantly moving around within Smart City according to their plans and consequently receive various network services from hosting devices adjacent. Currently, there are numbers of different types of security algorithms related to those activities; moreover, under such complexity of digital environment including various network devices and users, selective and customised services need to be provided for suitable purposes. However, the provided services are to be secured and well protected. Each customised service usually keeps tailored security policy and algorithm. Conventionally, every service including different servers, network, and users employs the same security algorithm so that sensitive information could be traced and revealed by using counter tracing method. Therefore, this paper investigates tailored smart security algorithm, which is taking into account scenarios within smart cities. Consequently, users are able to be protected under tailored security modules based on circumstances of network, smart devices, and types of services.